Morfología, taxonomía y caracterización de siete especies neotropicales del género Canna (Cannaceae-Zingiberales) - Ciciarelli, María de las Mercedes (2008)
Characters of rhizomes, leaves, inflorescences, flowers, pollen grains, and seeds of seven species of genus Canna were investigated in order to evaluate their diagnostic value. Species under study were: C. ascendens, C. coccinea, C. compacta, C. glauca, C. indica, C. paniculata y C. variegatifolia. The characters under study were rhizome branching; outline, size, apex, base, texture, surface, color of lamina margins and primary veins, types and distribution of indument, and venation patterns of leaves; types and length, length of basal internodes, number of axes and bracts per node, angles between axes, number of paracladia, color of bracts, sheaths and axes of the inflorescences; color, number of pieces, length of flowers and floral tubes, outline and rolling of labellum; size and ornamentation of exine of pollen grains; size, form, and color of seeds. Types of rhizomes, types of inflorescences, number of floral pieces, number and width of staminodia, position and rolling of labellum, color and size of seeds, characterize different groups of species. Foliar characters are diagnostic at the specific level, and when used together, allow identifying species in the absence of flowers. Indument is rare in Canna, and was found only in C. compacta and C. paniculata. Specific floral characters are color, size of flowers, and length of floral tube. Outline and apex of staminodia, and apex of labellum vary in flowers of the same individual, and have not diagnostic value. Echinate, inaperturate pollen grains were found in all taxa, with specific differences in size of grains, density, and length of spines. Phenotypic variation among individuals of each colony is frequent in the genus, and using combination of several characters seem to be the best via to recognize, and describe the taxa. Species under study were newly described, and dates on their taxonomy, geographical distribution, ecology, and a key to identify them are also given.